Revealed symmetric comparative advantage of global medical product exports - Ismail, Normaz Wana; Idris, Zera Zuryana; Utit, Chakrin; Lee, Chin (Human Resource Management Academic Research Society, 2024)
This study investigates the comparative advantages of medical product exportation among the leading exporters. We extend the traditional Balassa index by applying a revealed symmetric comparative advantage (RSCA) index that corrects the asymmetry in measuring exports’ comparative advantages or disadvantages. This study includes four groups of medical export products: medicines, medical supplies, medical equipment and technology, and personal protective equipment (PPE). We analyze data from the top 24 exporters in the world, which account for more than 80% of the export value spanning from 2015 to 2019. The findings indicate that high-income countries, specifically Switzerland, Japan, and Denmark, have a leading comparative advantage in medicines, medical supplies, and medical equipment and technology; however, China, Hong Kong, and the Czech Republic are among the leading producers of PPE. These findings provide a foundation for policy formulation to develop sustainable healthcare capacities.